2009
DOI: 10.1177/008124630903900102
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Test Battery for the Selection of Call Centre Operators in a Communications Company

Abstract: Our aim was to determine whether personality and ability measures can predict job performance of call centre operators in a South African communications company. The predictors were personality variables measured by the Customer Contact Styles Questionnaire, Basic Checking and Audio Checking ability tests. These measures were completed by 140 operators. Supervisors completed the Customer Contact Competency Inventory for the operators as a measure of job performance. Additional criterion data were utilised by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The most frequently measured constructs in the selection process are applicant personality traits and cognitive ability (Ng & Sears, 2010;Van Vianen & Van Schie, 1995) because they have shown to predict later job performance (Barrick & Mount, 1991;Dunn, Mount, Barrick, & Ones, 1995;Nicholls & Visser, 2010;Schmidt & Hunter, 1998;Tews, Stafford, & Tracey, 2011). While cognitive ability and conscientiousness predict job performance in all job categories (Schmidt & Hunter, 1998), extraversion is a valid predictor for jobs requiring social interactions (Barrick & Mount, 1991).…”
Section: Brunswikian Perspective Towards Encoding and Decodingmentioning
confidence: 99%
“…The most frequently measured constructs in the selection process are applicant personality traits and cognitive ability (Ng & Sears, 2010;Van Vianen & Van Schie, 1995) because they have shown to predict later job performance (Barrick & Mount, 1991;Dunn, Mount, Barrick, & Ones, 1995;Nicholls & Visser, 2010;Schmidt & Hunter, 1998;Tews, Stafford, & Tracey, 2011). While cognitive ability and conscientiousness predict job performance in all job categories (Schmidt & Hunter, 1998), extraversion is a valid predictor for jobs requiring social interactions (Barrick & Mount, 1991).…”
Section: Brunswikian Perspective Towards Encoding and Decodingmentioning
confidence: 99%
“…Van der Linde's (2005) study indicated a relationship between work performance measured by the level of financial incentives of agents and five personality traits namely, (1) analytical thinking, (2) detail consciousness, (3) conscientiousness, (4) 'structuredness' and (5) work performance. Nicholls (2006) utilised the same instrument as Van der Linde (2005) and found small to moderate correlations between personality tiaits and performance, and moderate to high correlations between abiUty and performance. Ojha and Kasturi (2005) fotmd that agents who experience high intrinsic motivation in their work and those that were team players achieve high levels of performance.…”
Section: Agent Competencementioning
confidence: 99%
“…Emotional intelligence correlated strongly with performance (Higgs, 2004;Nel & De Villiers, 2004). Personality aspects were also linked to performance (Möller et al, 2004;Nicholls, 2006;Ojha & Kastiari, 2005;Van der Linde, 2005).…”
Section: Agent Competencementioning
confidence: 99%
“…The most frequently measured constructs in the selection process are applicant personality traits and cognitive ability (Ng & Sears, 2010;Van Vianen & Van Schie, 1995) because they have shown to predict later job performance (Barrick & Mount, 1991;Dunn, Mount, Barrick, & Ones, 1995;Nicholls & Visser, 2010;Schmidt & Hunter, 1998;Tews, Stafford, & Tracey, 2011). While cognitive ability and conscientiousness predict job performance in all job categories (Schmidt & Hunter, 1998), extraversion is a valid predictor for jobs requiring social interactions (Barrick & Mount, 1991).…”
Section: Brunswikian Perspective Towards Encoding and Decodingmentioning
confidence: 99%